2022
DOI: 10.1038/s41598-022-09699-4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of SARS-CoV-2 antibodies using dried blood spot for at-home collection

Abstract: The utilization of vaccines to fight the spread of SARS-CoV-2 has led to a growing need for expansive serological testing. To address this, an EUA approved immunoassay for detection of antibodies to SARS-CoV-2 in venous serum samples was investigated for use with dried blood spot (DBS) samples. Results from self-collected DBS samples demonstrated a 98.1% categorical agreement to venous serum with a correlation (R) of 0.9600 while professionally collected DBS samples demonstrated a categorical agreement of 100.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Overall, the study results show a correlation of r > 0.96 for DBS and serum for both SARS-CoV-2 antibodies, S1 and NCP. Our results are in accordance with other work, presenting similarly high correlation for both materials regarding SARS-CoV-2 antibody analysis [ 13 , [16] , [17] , [18] ]. Suitability of DBS for analysis of SARS-CoV-2 antibodies was also shown using assays from other suppliers [ 19 , 20 ], as well as in-house methods or manual testing [ 9 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, the study results show a correlation of r > 0.96 for DBS and serum for both SARS-CoV-2 antibodies, S1 and NCP. Our results are in accordance with other work, presenting similarly high correlation for both materials regarding SARS-CoV-2 antibody analysis [ 13 , [16] , [17] , [18] ]. Suitability of DBS for analysis of SARS-CoV-2 antibodies was also shown using assays from other suppliers [ 19 , 20 ], as well as in-house methods or manual testing [ 9 , 21 , 22 ].…”
Section: Discussionsupporting
confidence: 93%
“…DBS sampling has the following advantages: (1) it does not require the separation of plasma from blood; (2) it can be performed with a smaller volume of blood than conventional blood tests, allowing self-collection of blood; and (3) the sample can be easily transported to the measurement facility [ 12 14 ]. As a simple sampling method, it is often used for newborn mass screening [ 12 ], and recently, its application to detect SARS-CoV-2 antibodies is also being considered [ 15 ]. However, DBS is sensitive to storage conditions, and the stability of some target substances may be compromised [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This simple and inexpensive method is suited for the study of SARS-CoV-2 seroprevalence, particularly where there is a lack of trained healthcare staff or geographically dispersed populations. Furthermore, a recent study has reported that when the samples are professionally collected, the categorical agreement between anti-SARS-CoV-2 antibodies obtained from dried blood spots and venous serum only increases by 2% from >98% to 100%, validating this monitoring method for at-home collection [ 29 ]. Another benefit of the finger-stick blood test is that it can be adapted for assessing the neutralizing antibody response against wild-type, alpha, beta, gamma, and delta variant RBDs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%